Dielectric Dispersion and High Field Response of Multilayer Hexagonal Boron Nitride. (10th August 2018) - Ahmed, Faisal; Heo, Sunwoo; Yang, Zheng; Ali, Fida; Ra, Chang Ho; Lee, Ho‐In; Taniguchi, Takashi; Hone, James; Lee, Byoung Hun; Yoo, Won Jong
Abstract: The dielectric dispersion of a material holds significant importance for the understanding of basic material characteristics and the design parameters of a functional device. Here, the dielectric dispersion characteristics of multilayer hexagonal boron nitride (hBN) using time domain reflectometry under an extended device operating frequency range up to 100 MHz are studied. Contrary to what is previously reported, the capacitance, hence the effective dielectric constant, of hBN decreases with the increase of frequency above the MHz range, indicating heat dissipation in lossy hBN dielectric. Furthermore, hBN shows stubborn dielectric characteristics with temperature changes that confirm its thermal stability in extreme operating conditions. The charge carriers in hBN are transported by Fowler–Nordhiem tunneling with increasing the electrical field. Lastly, hBN endures electrical field of 7.8 MV cm −1 that implies its potential use as a promising dielectric material. These results will benefit the research and development of hBN supported high‐speed electronics operated at high‐frequency conditions for energy‐efficient device applications. Abstract : The dielectric dispersion of 2D hexagonal boron nitride is studied under extended frequency by time domain reflectometry. It shows a decreasing dispersion characteristic beyond MHz frequency range, denoting heat dissipation in lossy hBN dielectric.